Stage-dependent effects of intermittent hypoxia influence the outcome of hippocampal adult neurogenesis - Maggie A. Khuu (Nature Portfolio, 2021)
Abstract Over one billion adults worldwide are estimated to suffer from sleep apnea, a condition with wide-reaching effects on brain health. Sleep apnea causes cognitive decline and is a risk factor for neurodegenerative conditions such as Alzheimer’s disease. Rodents exposed to intermittent hypoxia (IH), a hallmark of sleep apnea, exhibit spatial memory deficits associated with impaired hippocampal neurophysiology and dysregulated adult neurogenesis. We demonstrate that IH creates a pro-oxidant condition that reduces the Tbr2+ neural progenitor pool early in the process, while also suppressing terminal differentiation of adult born neurons during late adult neurogenesis. We further show that IH-dependent cell-autonomous hypoxia inducible factor 1-alpha (HIF1a) signaling is activated in early neuroprogenitors and enhances the generation of adult born neurons upon termination of IH. Our findings indicate that oscillations in oxygen homeostasis, such as those found in sleep apnea, have complex stage-dependent influence over hippocampal adult neurogenesis.